2012
DOI: 10.2174/157489112803521995
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature Plasma - a Prospective Microbicidal Tool

Abstract: The effects of low-temperature plasma treatment on microorganisms typically related to skin diseases are studied qualitatively by the inhibition of growth and viability assays to evaluate the potential for classifying as a prospective antiseptic agent. A variety of microorganisms enveloping gram- negative and gram-positive bacteria as well as one genus of yeast and fungus each were exposed to plasma in vitro. In a comparative approach, two power supplies, both of which produce high voltage pulses yet at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…One of them generated pulses in the microsecond range; the second device generates pulses in the nanosecond range. Some results of this study have already been published in ref . Investigations of other authors indicated a higher efficacy of nanosecond plasma sources in terms of the decontamination capacity …”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…One of them generated pulses in the microsecond range; the second device generates pulses in the nanosecond range. Some results of this study have already been published in ref . Investigations of other authors indicated a higher efficacy of nanosecond plasma sources in terms of the decontamination capacity …”
Section: Introductionsupporting
confidence: 61%
“…The gram‐negative bacteria as well as the yeast showed damages in the functional and in the morphological structure (see also). This can be explained by lipid peroxidation of the cell membrane caused by strong oxidizers like OH radicals and H 2 O 2 .…”
Section: Resultsmentioning
confidence: 89%
“…Various effects induced by CAP have been observed. Consistently, a reduction in a wide range of microorganisms was found in vitro and in vivo by groups all over the globe . Further effects include the induction of angiogenesis, stimulation or inhibition of cell proliferation, up‐ and downregulation of genes in skin cells, and virus inactivation …”
Section: Introductionmentioning
confidence: 60%
“…Consistently, a reduction in a wide range of microorganisms was found in vitro and in vivo by groups all over the globe. [16][17][18][19][20][21][22][23] Further effects include the induction of angiogenesis, 24 stimulation or inhibition of cell proliferation, 25 up-and downregulation of genes in skin cells, 26 and virus inactivation. 27 Recent studies have revealed a significant impact of short-term diCAP application (up to 90 seconds) on the microcirculation of skin.…”
mentioning
confidence: 99%
“…In particular, the NO-loading effects, skin acidification, increase of dermal microcirculation and known antimicrobial effects [34] could have a clinical relevance. However, to prove the efficacy of DBD devices as NO donor systems in therapies, further studies and clinical trials are necessary.…”
Section: Article In Pressmentioning
confidence: 99%